An Embedded Level-Shifting Dual-Rail SRAM for High-Speed and Low-Power Cache - Tae Hyun Kim; Hanwool Jeong; Juhyun Park; Hoonki Kim; Taejoong Song; Seong-Ook Jung (IEEE Access, 2020)
An embedded level-shifting (ELS) dual-rail SRAM is proposed to enhance the availability of dual-rail SRAMs. Although dual-rail SRAM is a powerful solution for satisfying the increasing demand for low-power applications, the enormous performance degradation at low supply voltages cannot meet the high-performance cache requirement in recent computing systems. The requirement of many level shifters is another drawback of the dual-rail SRAM because it degrades the energy-savings. The proposed ELS dual-rail SRAM achieves energy-savings by using a low supply voltage to precharge bitlines while minimizing the performance overhead by appropriately assigning a high-supply voltage to critical circuit blocks with effective level-shifting circuits. The sense amplifier embeds a level-shifting operation, thereby operating with a high supply voltage for a fast sensing operation. The proposed dynamic output buffer resolves the potential static current problem and improves the read delay. The number of level shifters is reduced using a proposed write driver, which conducts level-shifting and write-driving simultaneously. The proposed ELS dual-rail SRAM achieves low-power operation with 71.4% power consumption compared to single-rail SRAM with 72% performance overhead in circuit-level simulation, while the previous hybrid dual-rail SRAM shows 67.8% energy consumption with 270% performance overhead. In architecture-level simulation using Gem5 simulator with SPEC2006 benchmarks, the system with the ELS dual-rail SRAM caches shows, on average, 29% performance improvement compared to that of the system with the hybrid dual-rail SRAM caches.